Thermal Effects in Slender EHL Contacts - Marko Tošić; Roland Larsson; Thomas Lohner (Lubricants, 2022)
This study deals with experimental and numerical analysis of the thermal effects of slender elastohydrodynamically lubricated (EHL) contacts under high sliding. Thereby, the entrainment direction is along the major axis of the contact ellipse. Film thickness measurements were carried out on an optical EHL tribometer with a glass disk and steel roller. Numerical EHL solutions were obtained with consideration for non-Newtonian rheology and thermal effects. The results show that thermal effects can result in a strong viscosity wedge diverting oil flow to the contact sides. For high positive sliding, in which the glass disk moves faster, the influence of entrainment speed on minimum film thickness is almost negligible, while the film thickness shows a continuous decrease in gap length direction.